Magnetic behavior of interstitial Fe impurities in divalent Ca, Sr, and Yb hosts - de Mello, L. A.; Frota-Pessoa, S. (American Physical Soc, 2000)
We have used a first-principles real-space approach to investigate the electronic structure and the magnetic behavior of interstitial Fe impurities in divalent Ca, Sr, and Yb hosts. The dependence of the local moment as a function of lattice relaxation around the impurity is obtained and contrasted with that of interstitial Fe in trivalent and tetravalent Zr, Y, Ti, and Sc hosts. The trends obtained for local moment formation at the impurity site an in agreement with experimental time-differential perturbed gamma-ray angular distribution technique observations.